1982
DOI: 10.1128/aem.44.6.1335-1341.1982
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Distribution of and Bioemulsifier Production by Acinetobacter calcoaceticus BD4 and BD413

Abstract: The heavily encapsulated Acinetobacter calcoaceticus BD4 and the "miniencapsulated" single-step mutant A. calcoaceticus BD413 produced extracellular polysaccharides in addition to the capsular material. The molar ratio of rhamnose to glucose (3:1) in the extracellular BD413 polysaccharide fraction was similar to the composition of the capsular material. In both strains, the increase in capsular polysaccharide was parallel to cell growth and remained constant in stationary phase. The extracellular polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…1). The results also indicated that the requirement for Mg 2+ (15 ppm) is low in comparison with other biosurfactant-producing bacteria (19).…”
Section: Resultsmentioning
confidence: 79%
“…1). The results also indicated that the requirement for Mg 2+ (15 ppm) is low in comparison with other biosurfactant-producing bacteria (19).…”
Section: Resultsmentioning
confidence: 79%
“…Aeinetobacter ealcoaceticus ATCC 14987 was obtained from the Ameriean Type Culture Collection, Rockville, MD, U.S.A. The organism was grown in minimal medium (Kaplan & Rosenberg, 1982) suppletnented with 2kg m"-' (w/v) easamino aeids (Difeo). Cells in late exponential phase of growth were harvested by eentrifugation, washed with 50 mol m"-' K phosphate (pH 7.0) eontaining 1 mol m~-^ dithiothreitol (DTT) (Buffer C) and were stored at -70°C until used.…”
Section: Bacterial Growth Extract Preparation and Enzyme Assaysmentioning
confidence: 99%
“…Ac. calcoaceticus BD4 and BD413, ATCC 17294, ATCC 17906, were also investigated for emulsi®er production (Kaplan and Rosenberg 1982;Kaplan et al 1987). However, there is no report of bioemulsi®er production by Acinetobacter strains from human skin.…”
Section: Introductionmentioning
confidence: 99%